The Effect of Financial Literacy on Consumptive Behavior of Managerial Accounting Study Program Students in Batam State Polytechnic - Kurniawan, Dedi; Pasaribu, M. Hafizh Bakrin; Parinduri, Annisya Fitri Khairina; Mohamed, Saeed Hasan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research was conducted in order to determine the effect of financial literacy on the consumptive behaviour of students of the Batam State Polytechnic Managerial Accounting Study Program. Quantitative research is the method used in this research. This research obtained data by distributing questionnaires using a Likert Scale. The population in this research were 161 students, and using a sampling technique, namely purposive sampling, the respondents who were sampled in this research were students of the Batam State Polytechnic of Batam State Polytechnic Study Program with 64 respondents. This research uses simple linear regression as a data analysis technique, this analysis is carried out through the use of the SPSS version 20 program. The results showed that financial literacy significantly negatively affected the consumptive behaviour of students of the Batam State Polytechnic of Managerial Accounting Study Program.